2019
DOI: 10.1101/595355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural dynamics of the attentional blink revealed by encoding orientation selectivity during rapid visual presentation

Abstract: The human brain is inherently limited in the information it can make consciously accessible. When people monitor a rapid stream of visual items for two targets, they can typically report the first, but not the second target, if these appear within 200-500 ms of each other, a phenomenon known as the attentional blink (AB). No work has determined the neural basis for the AB, partly because conventional neuroimaging approaches lack the temporal resolution to adequately characterise the neural activity elicited by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 72 publications
(129 reference statements)
5
49
0
Order By: Relevance
“…Our findings corroborate previous work showing that multiple sensory representations can coexist in patterns of neural activity for a few hundred milliseconds, presumably at different (early) stages of processing (Grootswagers et al, 2019;Marti & Dehaene, 2017;Tang et al, 2020). Temporal decoding profiles of target and distractor stimuli were robust and remarkably similar up to approximately 250 ms, confirming that early stages of visual processing are common to all stimuli -seen or unseen -entering the visual system, while late-stage processing is selective to consciously perceived stimuli (Marti & Dehaene, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings corroborate previous work showing that multiple sensory representations can coexist in patterns of neural activity for a few hundred milliseconds, presumably at different (early) stages of processing (Grootswagers et al, 2019;Marti & Dehaene, 2017;Tang et al, 2020). Temporal decoding profiles of target and distractor stimuli were robust and remarkably similar up to approximately 250 ms, confirming that early stages of visual processing are common to all stimuli -seen or unseen -entering the visual system, while late-stage processing is selective to consciously perceived stimuli (Marti & Dehaene, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Previous fMRI studies have shown enhanced T2 processing in T2-seen trials, in frontal and parietal areas as well as in low-level visual areas, such as the primary visual cortex (Hein, Alink, Kleinschmidt, & Müller, 2009;Slagter, Johnstone, Beets, & Davidson, 2010;Williams, Visser, Cunnington, & Mattingley, 2008). Using EEG, Tang et al (2020), as noted above, also observed differences in early T2 orientation representation between blink and no-blink trials, within 100-150ms post-T2. Yet, here, while we could decode T2 number identity peaking around 170 ms, we could do so equally well in T2 blink and no-blink trials.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations